Epidemiological Surveillance over HIV-infection among Blood Donors, Medical Practitioners in the Far Eastern Federal District (2008–2017) - E. A. Bazykina; V. B. Turkutyukov; O. E. Trotsenko (Эпидемиология и вакцинопрофилактика)
The objective of the research was to conduct a comparative analysis of HIV detection frequency in blood donors, medical practitioners and general population of the Far Eastern Federal district. Materials and methods. Analysis of the obtained data included general statistical methods involving parametric and nonparametric statistics. Results. During the years 2008–2017, an increase in medical examination coverage concerning citizens HIV-status was detected. The index in the Far Eastern Federal district in 2017 averaged 22.81 ± 0.02%. A moderate accession rate (2.86%) of HIV-infection cases detection was registered among blood donors during the studied period of time. In the group of medical practitioners HIV-infection accession rate was low (0.8%) and the trend can be characterized as relatively stable. Should be noted that HIV-infection among medical staff was not associated with professional performance. No correlation was registered between HIV abundance in general population, blood donors and medical practitioners of the Far Eastern Federal district. This fact potentially indicates on the isolation of the epidemiological process in blood donors and medical practitioners. Conclusion. Preventive work against HIV-infection and other hemotransmissive diseases among medical staff and general population needs to be strengthened in order to increase awareness concerning transmission routs of the infections and existing preventive measures.